2020
DOI: 10.3390/molecules25061341
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols from Salix tetrasperma Impair Virulence and Inhibit Quorum Sensing of Pseudomonas aeruginosa

Abstract: Bacterial resistance represents one of the emerging obstacles in plants, animals, and humans that impairs treatment with antibacterial agents. Targeting of the bacterial quorum sensing system is one of the strategies to overcome this problem. Recently, research has been focused on natural and food components which can function as quorum sensing inhibitors. In this study, a methanol extract from Salix tetrasperma stem bark was phytochemically profiled by LC-MS analysis. This resulted in the identification of 38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 45 publications
6
47
0
Order By: Relevance
“… Snoussi et al (2018) have reported that the essential oils and phenolics of Carum copticum inhibit violacein production. Similar results also have been reported for the phenolic compounds from plants ( Mostafa et al, 2020 ). There are three QS systems in bacteria: the LuxR/I-type systems, typically used by Gram-negative species, in which the signaling molecule is an N -acyl L -homoserine lactone (AI-1); the small oligopeptides (AIP) systems, typically used by Gram-positive species; and the LuxS/furanone metabolites (AI-2) interspecies signaling systems ( Galloway et al, 2011 ; Hawver et al, 2016 ).…”
Section: Discussionsupporting
confidence: 90%
“… Snoussi et al (2018) have reported that the essential oils and phenolics of Carum copticum inhibit violacein production. Similar results also have been reported for the phenolic compounds from plants ( Mostafa et al, 2020 ). There are three QS systems in bacteria: the LuxR/I-type systems, typically used by Gram-negative species, in which the signaling molecule is an N -acyl L -homoserine lactone (AI-1); the small oligopeptides (AIP) systems, typically used by Gram-positive species; and the LuxS/furanone metabolites (AI-2) interspecies signaling systems ( Galloway et al, 2011 ; Hawver et al, 2016 ).…”
Section: Discussionsupporting
confidence: 90%
“…The extract inhibited the biofilm formation of P. aeruginosa in a dose-dependent manner and ranged from 17 to 38% ( Figure 5 ). These considerable antibiofilm properties are similar to that of polyphenol-rich extract from the bark of Salix tetrasperma and the leaves of Annona glabra and Gynura procumbens [ 54 , 55 , 56 ]. A recent study by Koely et al described the antibiofilm activities of Enydra fluctuans against P. aeruginosa .…”
Section: Resultsmentioning
confidence: 84%
“…The inhibition of biofilm is considered an important way for the treatment of bacterial infections [8]. Searching for bacterial virulence factors inhibitors is very important due to the well-known ability of pathogens to develop different mechanisms of antibiotics resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Plant extracts have been reported to regulate biofilm formation and inhibit quorum sensing (QS) [5]. Various studies have explored different natural secondary metabolites to prevent the formation of biofilms in Gram-negative and Gram-positive bacteria, in addition to the dimorphic pathogenic yeast [4,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%